Evaluating the Role of Accounting Information Systems in Enhancing Village Financial Governance: a Study From Jayapura City - Adolf Z D. Siahay; Theo Allolayuk; Manggalawati Tande Bura (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study aims to evaluate the role of Accounting Information Systems (AIS) in improving the effectiveness, transparency, and accountability of village financial management in Jayapura City. The main issues raised are the weak financial management of villages, limited human resource capacity, and the uneven implementation of AIS across villages. This study uses a mixed methods approach, combining qualitative interviews with village officials and quantitative analysis of the effectiveness ratio of village expenditure realisation for 2020–2024. Qualitative results show that most villages have implemented SIA based on Siskeudes, which has improved recording accuracy and administrative efficiency, although there are variations due to differences in training, infrastructure, and socio-cultural factors. Quantitative analysis shows that the average expenditure realisation exceeds 90% in most villages, reflecting a high level of financial management effectiveness. However, spending priorities are still dominated by administrative and physical development expenditures, with low allocations for community empowerment. The results of this study emphasise the importance of increasing the capacity of the apparatus, preparing a balanced budget, and providing stronger regulatory support in order to optimise the implementation of the SIA and encourage sustainable village development.